Ball milling induced strong polarization electric fields in Cu3B2O6 crystals for high efficiency piezocatalysis. (April 2022) - Liao, Xiaomin; Xie, Huiyuan; Liao, Biru; Hou, Sen; Yu, Yang; Fan, Xiaoyun
Abstract: Harvesting mechanical energy by piezocatalyst from ultrasonication offers an unprecedented opportunity for environment remediation. However, the piezocatalytic efficiency is seriously hindered by current catalysts and the harvest of energy. Herein, for the first time, by agitation of a kind of borate like Cu3 B2 O6 (CBO) material through ball milling (BM) could decompose pollutants efficiently. The efficiency of CBO for Rhodamine B under BM is 6.4 times that of benchmark BaTiO3, and 10.4 times that of CBO under ultrasonication. Moreover, CBO also exhibits an excellent performance for the inactivation of Escherichia coil K-12 and a good catalytic cycle stability. The high catalytic efficiency can be attributed to the formed strong piezoelectric field in CBO and abundant reactive species generated under BM. The results give an insight into the development of high efficient piezocatalytic reactions based on the piezocatalysts and BM combined strategy. Graphical Abstract: We demonstrate the first example of a kind of nonlinear optical material, Cu3 B2 O6 (CBO) material that mediates the conversion of mechanical energy to chemical redox reaction through ball milling. The water pollutants, Rhodamine B and Escherichia coil K-12, could be decomposed completely in the presence of CBO material. This material exhibits a strong polarization electric field and high free charges separation efficiently when exerted to a high mechanical force. ga1 Highlights: A borate piezoelectric and BM combined strategy for the high efficient piezocatalytic. The rate constant of CBO is 6.4 times that of benchmark BaTiO3 under BM for Rhodamine B degradation. The BM setup can efficiently achieve water disinfection. The high speed stirring generates abundant reactive species. BM induced strong piezoelectric field is beneficial for the free charges separation.